OPTIMIZATION STRATEGY TO REDUCE UNEMPLOYMENT ON THE IMPACT OF THE DEMOGRAPHIC BONUS IN TANGERANG CITY - Timur, Aini; Rivai, Firman Hadi; Giyanto, Bambang (DIA: Jurnal Administrasi Publik, 2024)
The high unemployment rate is a challenge in achieving sustainable economic growth and social welfare. With the increasing population, dominated by people of productive age, Tangerang City is currently experiencing a demographic bonus. Therefore, this research aims to analyze the factors that influence the unemployment rate from the conditions of employment opportunities in Tangerang City. From the identification of these factors, it is important to formulate an optimization strategy to reduce unemployment on the impact of the demographic bonus. This research uses a descriptive and qualitative approach using primary and secondary data. The research results show that factors such as disparities between demand and availability of labor, conditions of employment opportunities, and barriers to finding work influence the unemployment rate in Tangerang City. Apart from that, there are also factors such as stakeholder involvement, job market needs, and the quality of human resources which play a role in influencing the unemployment rate. This research provides insight and policy recommendations to reduce the unemployment rate in Tangerang City.